1992
DOI: 10.1136/gut.33.12.1633
|View full text |Cite
|
Sign up to set email alerts
|

Endomysial antibody: is it the best screening test for coeliac disease?

Abstract: The sensitivities and specificities of the IgA and IgG antigliadin antibody and the IgA antireticulin antibody have been compared with the recently described endomysial antibody directed against the basement membrane of smooth muscle in monkey oesophagus. One hundred and seventeen patients with adult coeliac disease (21 untreated), 84 patients with inflammatory bowel disease, systemic lupus erythematosus and rheumatoid arthritis (comprising the disease control group), 47 normal controls and a miscellaneous gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(124 citation statements)
references
References 28 publications
7
113
0
4
Order By: Relevance
“…The best serological approach to diagnose CD is based on the EmA and anti-tTG assays, which have a very high diagnostic accuracy [4][5][6]16,17]. However, these serological tests do not correlate with histopathological features [8,18] and only recently another test -the AAA assay -has been proposed as a marker of the severity of intestinal mucosa damage in CD [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best serological approach to diagnose CD is based on the EmA and anti-tTG assays, which have a very high diagnostic accuracy [4][5][6]16,17]. However, these serological tests do not correlate with histopathological features [8,18] and only recently another test -the AAA assay -has been proposed as a marker of the severity of intestinal mucosa damage in CD [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…It is nowadays evident that CD is one of the most common life-long diseases, with a frequency around 1:100-1:200 in the general population [1][2][3]. The enormous increase in CD diagnoses in recent decades is in large part due to the availability of serum tests with excellent diagnostic accuracy, such the anti-endomysium and antitransglutaminase assays [4][5][6]. However, these assays do not reflect the severity of the intestinal mucosa damage [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that EmA was 100% positive for untreated patients and for celiacs non-adhering to the diet and disagree with those reported by McMILLAN et al (50) who found that 89% of their patients with untreated celiac disease had a positive EmA measured by immunofluorescence. However, FERREIRA et al (26) showed 100% positivity to EmA for untreated celiac disease in a predominantly adult population similar to that studied here. The data of our study are in agreement with several authors from different countries, as can be seen in Table 4 (3,10,12,14,19,23,26,32,33,49,55,66,70) .…”
Section: Considerations About Emamentioning
confidence: 90%
“…The use of these tests can result in a dramatic increase in the prevalence of CD because asymptomatic forms can be detected (65) . The sensitivities and specificities of these tests varied from centre to centre but improved with the use of class specific immunoglobulins (IgA) (26) .…”
Section: Introductionmentioning
confidence: 99%
“…Antiendomysial antibody has been shown to have a high sensitivity and specificity for the diagnosis of celiac disease and correlates well with villous atrophy in untreated patients, but false-negative results have been obtained for patients with IgA deficiency, justifying its measurement (29)(30)(31)(32). However, an intestinal biopsy continues to be the Gold Standard for the diagnosis of celiac disease (6,7).…”
Section: Discussionmentioning
confidence: 99%